Development and validation of the Individual Potentials Questionnaire (IP-Q) - Sabo, Abdulwali; Kuan, Garry; Abdullah, Sarimah; Kuay, Hue San; Kueh, Yee Cheng (Scientific reports, 2025)
Individual potential has recently been acknowledged by the holistic health model as being essential to successfully addressing life’s demands, both now and in the future. The study employed a cross-sectional survey among Nigerian university undergraduate students, using a convenience sampling method, to assess their subjective individual potential. The study investigated the psychometric properties of the newly developed Individual Potentials Questionnaire (IP-Q). The study involved a total of 730 participants (EFA = 300 and CFA = 430). The I-CVIs and S-CVIs fall within the range of 0.83 to 1, and the I-FVIs and S-FVIs are 1. Two factors (biologically given potential and personally acquired potential) emerged in the EFA analysis, with all 14 items retained due to satisfactory factor loadings (above 0.50) and KMO = 0.905 ( p -value < 0.001). The final CFA model fit indices were: CFI = 0.984, TLI = 0.980, SRMR = 0.034, RMSEA = 0.041, and RMSEA p -value = 0.880. Furthermore, the ICCs for the test–retest are 0.976 (biologically given potential) and 0.953 (personally acquired potential). The results show that the newly developed IP-Q has adequate construct validity and able to assess subjective individual potential.